2016
DOI: 10.1371/journal.pone.0165306
|View full text |Cite
|
Sign up to set email alerts
|

Supercoiling Effects on Short-Range DNA Looping in E. coli

Abstract: DNA-protein loops can be essential for gene regulation. The Escherichia coli lactose (lac) operon is controlled by DNA-protein loops that have been studied for decades. Here we adapt this model to test the hypothesis that negative superhelical strain facilitates the formation of short-range (6–8 DNA turns) repression loops in E. coli. The natural negative superhelicity of E. coli DNA is regulated by the interplay of gyrase and topoisomerase enzymes, adding or removing negative supercoils, respectively. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…2013 ), nonB-DNA structures are expected to modify the process by relieving the torsional tension of nearby DNA, increasing the energy required for it to bend ( Benham etal. 2010 ; Mogil etal. 2016 ; fig.…”
Section: Links To Enhancer Functionmentioning
confidence: 99%
“…2013 ), nonB-DNA structures are expected to modify the process by relieving the torsional tension of nearby DNA, increasing the energy required for it to bend ( Benham etal. 2010 ; Mogil etal. 2016 ; fig.…”
Section: Links To Enhancer Functionmentioning
confidence: 99%
“…Several reports in the literature have shown that the probability of forming loops oscillates as a function of the rotational offset determined by the contour length between the binding sites ( 30–32 ). This may be important for loops between the O1 and O3 operators of the lac operon in E. coli , which are separated by a torsionally rigid 92 bp segment, and may be relevant to observations of the supercoiling-driven modulation of in vivo repression of a reporter gene by protein-mediated DNA loops 70–85 bp-long ( 33 ). As shown previously, supercoiling-induced and HU-stabilized kinks likely bent the segment and optimized the orientation of the binding sites enhanced the formation of the 113 bp loop mediated by the gal repressor ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…1G) in topoisomerase mutant strains exhibiting a global SC shift either in the direction of DNA relaxation (gyrB mutant) or SC increase (topA). This feature was reproduced using the experimentally measured SC levels of these strains [34], suggesting that the two A/Tricher mutant promoters have reached a plateau where the denaturation energy, and hence the expression level, is almost independent of SC.…”
Section: Resultsmentioning
confidence: 65%
“…In vivo SC levels used in the computations of Fig. 1 were taken from [20,16] (E. coli strains with norfloxacin), and [34] (topoisomerase mutants of E. coli). In the data of [19] (Fig.…”
Section: Superhelical Densitiesmentioning
confidence: 99%